Operations research and enterprise systems : 4th International Conference, ICORES 2015, Lisbon, Portugal, January 10-12, 2015, Revised selected papers /: 4th International Conference, ICORES 2015, Lisbon, Portugal, January 10-12, 2015, Revised selected papers. (2015) - Unknown
No abstract available